Effect of Health Promotion with Halma Simulation on Knowledge Level of Caries Prevention of 1st Grade Students of SDN 115 Turangga Bandung City - Enisah Enisah; Yuyun Sarinengsih; Imam Abidin; Wardhani Wardhani; Tita Rostiana (Science Midwifery, 2019)
World Health Organization (WHO) states that around 60-90% of school-aged children have teeth caries. From the data of Basic Health Research 2013, it is stated that teeth caries patients are 53.2%. In Bandung City, the caries rate is 53.9%, while in Puskesmas (Public Health Center) Cijagra Lama, the teeth caries incident rate on children that mostly occurs in SDN (Public Elementary School) 115 turangga is 89%. The objective of this research is to find out the effect of health promotion with modified halma simulation on the influence of health promotion with halma simulation on knowledge level of teeth caries prevention in 1st grade students of SDN 115 Turangga Bandung City. The type of this research is pretest-posttest one group design on a population of 46 children. The data collection technique is conducted with halma simulation and questionnaire. The data analysis used is univariate and bivariate with Wilcoxon Matched Pairs Test. The result of this research analysis shows that there is an effect of modified halma simulation health promotion on the level of knowledge in teeth caries prevention on those 1st graders, with p-value rate (2-tailed) is <0.05, and the significance level (.Sig) is 0.013. Based on the research result, it is necessary to conduct a further research on the behavior in preventing teeth caries on the higher grades.